Analysis of the Calculation of Profit Volume Costs, Break Even Points, Margin of Safety, and Contribution Margin on Profit Planning - Elidawati Elidawati; Edy Terdjo (Cahaya Abadi Publisher, 2026)
The rapid growth of the coffee shop industry in Indonesia has transformed coffee shops into a